Neuroinflammation in Bipolar Depression - Benedetti, Francesco; Aggio, Veronica; Pratesi, Maria Luisa; Greco, Giacomo; Furlan, Roberto (Frontiers in Psychiatry, 2020)
Bipolar Disorder (BD) is a leading cause of worldwide disability among mood disorders. Pathological mechanisms are still vastly unclear, and current treatments with conventional medications are often unsatisfactory in maintaining symptoms control and an adequate quality of life. Consequently, current research is focusing on shedding new light on disease pathogenesis, to improve therapeutic effectiveness. Recent evidence has suggested a prominent role of inflammation in mood disorders. Elevated levels of peripheral pro-inflammatory mediators have been reported in BD, as well as in other mood disorder, and people with systemic auto-immune disease have an increased risk of developing BD. These immunological alterations are stable, and current medications are unable to alter peripheral concentration even in case of a clinical improvement. Targeting microglial activation, these findings has been replicated also in central nervous system (CNS), whereas genetic studies shown that these immune alterations are not due to the disorder itself, being detectable before the illness onset. Moreover, these inflammatory modifications seem to be affected and linked also to other biomarkers of the disorder, such as alterations of white matter (WM) microstructure, metabolism, kynurenine pathway, and circadian rhythmicity. Finally, these immune variations seem to be useful as predictors of therapeutic responsiveness to medication, and in discriminating between clinically different outcomes. The objective of this review is to summarise available evidence on the connection between inflammation and BD, focusing on peripheral inflammatory markers and recent findings on their connection with other characteristic features of BD, in order to outline a general overview on the disorder. Moreover, it is meant to analyse the issues with data gathering and interpretation, given the partially contradictory and inconsistent nature of results.